2009
DOI: 10.1117/1.3216575
|View full text |Cite
|
Sign up to set email alerts
|

New technique for the visualization of high dynamic range infrared images

Abstract: We propose a new dynamic range compression technique for infrared (IR) imaging systems that enhances details visibility and allows the control and adjustment of the image appearance by setting a number of tunable parameters. This technique adopts a bilateral filter to extract a details component and a coarse component. The two components are processed independently and then recombined to obtain the output-enhanced image that fits the display dynamic range. The contribution made is threefold. We propose a new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 15 publications
0
31
0
2
Order By: Relevance
“…It outperforms histogram equalization, Fattal's method [10], and retinex algorithm [11] in the subjective tests. In [12], bilateral filter is used for the dynamic range compression of IR HDR images and the proposed algorithm is compared with histogram equalization and retinex algorithms [11]. An adaptive contrast IR enhancement method is proposed in [13] which uses a quantitative model and adaptive plateau histogram equalization.…”
Section: Related Workmentioning
confidence: 99%
“…It outperforms histogram equalization, Fattal's method [10], and retinex algorithm [11] in the subjective tests. In [12], bilateral filter is used for the dynamic range compression of IR HDR images and the proposed algorithm is compared with histogram equalization and retinex algorithms [11]. An adaptive contrast IR enhancement method is proposed in [13] which uses a quantitative model and adaptive plateau histogram equalization.…”
Section: Related Workmentioning
confidence: 99%
“…Balanced contrast limited adaptive histogram equalization and contrast enhancement techniques are used together for an improved visualization of the IR images [11] . A bilateral filter [12] is also used for the dynamic range compression of the IR HDR images. After a comparative analysis of the different techniques for sea surface scene, it is observed that the bilateral filtering provides somewhat better results in the tests among the compared methods.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, multiscale decomposition of the original image avoids introducing halo artifacts. Based on those advantages, Branchitta et al described a new idea for HDR compression and detail enhancement of an infrared image [19]. This method separates the original image into a base component and a detail component by BF, through which the two parts are either compressed or expanded independently.…”
Section: Introductionmentioning
confidence: 98%